The Polg Mutator Phenotype Does Not Cause Dopaminergic Neurodegeneration in DJ-1-Deficient Mice1,2,3 - Hauser, David N. (eNeuro, 2015)
Mutations in the DJ-1 gene cause autosomal recessive parkinsonism in humans. Several mouse models of DJ-1 deficiency have been developed, but they do not have dopaminergic neuron cell death in the substantia nigra pars compacta (SNpc). Mitochondrial DNA (mtDNA) damage occurs frequently in the aged human SNpc but not in the mouse SNpc. We hypothesized that the reason DJ-1-deficient mice do not have dopaminergic cell death is due to an absence of mtDNA damage. We tested this hypothesis by crossing DJ-1-deficient mice with mice that have similar amounts of mtDNA damage in their SNpc as aged humans (Polg mutator mice). At 1 year of age, we counted the amount of SNpc dopaminergic neurons in the mouse brains using both colorimetric and fluorescent staining followed by unbiased stereology. No evidence of dopaminergic cell death was observed in DJ-1-deficient mice with the Polg mutator mutation. Furthermore, we did not observe any difference in dopaminergic terminal immunostaining in the striatum of these mice. Finally, we did not observe any changes in the amount of GFAP-positive astrocytes in the SNpc of these mice, indicative of a lack of astrogliosis. Altogether, our findings demonstrate the DJ-1-deficient mice, Polg mutator mice, and DJ-1-deficient Polg mutator mice have intact nigrastriatal pathways. Thus, the lack of mtDNA damage in the mouse SNpc does not underlie the absence of dopaminergic cell death in DJ-1-deficient mice.